Receptor-type guanylyl cyclase Gyc76C is required for development of the Drosophila embryonic somatic muscle. - Patel, U.; Davies, S.A.; Myat, M.M. (Biology open, 2012)
Guanylyl cyclases mediate a number of physiological processes, including smooth muscle function and axonal guidance. Here, we report a novel role for Drosophila receptor-type guanylyl cyclase at 76C, Gyc76C, in development of the embryonic somatic muscle. In embryos lacking function of Gyc76C or the downstream cGMP-dependent protein kinase (cGK), DG1, patterning of the somatic body wall muscles was abnormal with ventral and lateral muscle groups showing the most severe defects. In contrast, specification and elongation of the dorsal oblique and dorsal acute muscles of gyc76C mutant embryos was normal, and instead, these muscles showed defects in proper formation of the myotendinous junctions (MTJs). During MTJ formation in gyc76C and pkg21D mutant embryos, the ?PS integrin subunit failed to localize to the MTJs and instead was found in discrete puncta within the myotubes. Tissue-specific rescue experiments showed that gyc76C function is required in the muscle for proper patterning and ?PS integrin localization at the MTJ. These studies provide the first evidence for a requirement for Gyc76C and DG1 in Drosophila somatic muscle development, and suggest a role in transport and/or retention of integrin receptor subunits at the developing MTJs.